2005
DOI: 10.1182/blood-2004-04-1441
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic inhibitory killer immunoglobulin-like receptor ligand incompatibility enhances the long-term antileukemic effect of unmodified allogeneic hematopoietic stem cell transplantation in patients with myeloid leukemias

Abstract: It remains controversial whether alloreactive donor-derived natural killer (NK) cells display graft-versus-leukemia reactions after unmodified allogeneic hematopoietic stem cell transplantation (HSCT). The present study evaluated the role of inhibitory killer immunoglobulin-like receptor (KIR) ligand incompatibility using a welldefined and uniform setting of unmodified allogeneic HSCT in 374 patients with myeloid leukemias. The most striking finding was a significant heterogeneity in the 5-year estimates of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
2
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 35 publications
4
111
2
5
Order By: Relevance
“…Giebel et al 7 supported the concept raised by Velardi et al, 4,5 Beelen et al 8 only confirmed the antileukaemic effect whereas others reported no benefit from mismatches that should have favoured NK-cell alloreactivity. [9][10][11] A recent study 12 reported an improved outcome in patients transplanted for AML and myelodysplastic syndrome (MDS) with T-depleted HLA-identical sibling bone marrow and lacking an HLA ligand for donor inhibitory KIR.…”
Section: Introductionsupporting
confidence: 66%
“…Giebel et al 7 supported the concept raised by Velardi et al, 4,5 Beelen et al 8 only confirmed the antileukaemic effect whereas others reported no benefit from mismatches that should have favoured NK-cell alloreactivity. [9][10][11] A recent study 12 reported an improved outcome in patients transplanted for AML and myelodysplastic syndrome (MDS) with T-depleted HLA-identical sibling bone marrow and lacking an HLA ligand for donor inhibitory KIR.…”
Section: Introductionsupporting
confidence: 66%
“…In subsequent studies of related or unrelated HSCT, NK cell-mediated effects were less clear-cut. Whereas a beneficial influence of KIR ligand mismatching on leukemic relapse as well as survival was observed in some studies (8,9), similar effects were not seen in others (10,11). Recently, a combined analysis of KIR ligands together with DNAor RNA-based KIR typing was suggested as better predictors of clinical outcome (12,13).…”
Section: Relevance Of C1 and C2 Epitopes For Hemopoietic Stem Cell Trmentioning
confidence: 93%
“…HLA-A and -B polymorphisms were determined by low-and intermediateresolution DNA-based typing using PCR-sequence-specific primer (SSP) typing as described previously (9). Additionally, to enable unambiguous assignment of HLA-C-encoded KIR ligands, HLA-C alleles were determined by DNA-based direct sequencing in all donors and recipients included in this study.…”
Section: Genotyping For Hla and Kirmentioning
confidence: 99%
“…30,31 Although these findings were confirmed by some groups, others failed to show any benefit. [32][33][34][35][36][37][38] Results of those studies are discussed in more detail elsewhere by Verheyden and Demanet. 39 Another NK cell escape mechanism demonstrated in the HSCT setting is the overexpression of the inhibitory receptor CD94/ NKG2A on reconstituted NK cells that recognizes human leukocyte antigen-E on AML blasts, which is associated with a low cytotoxic capacity.…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%